A STUDY ON SECURE PRIVATE SET UNION SCHEME IN IOT ENVIRONMENT - Ki-Hwan Kim; Su-Hyun Kim; Im-Yeong Lee (MATTER: International Journal of Science and Technology, 2025)
In the IOT environment, network edges have data, but a centralized server may need to obtain the union from edges for efficient data access. PSU is a cryptographic primitive that allows protocol parties to compute the union of their private datasets without revealing any extra information. Traditional PSU protocols presuppose that all parties must input their private datasets. This assumption doesn’t hold in some scenarios where an inputless Third party needs to get the union. For instance, a regulatory organization may need to get the union of patient data from hospitals for statistical analysis, without inputting any dataset. We propose a novel TP-PSU, specifically designed for a setting with three parties and an inputless Third party. Our protocol enables the Third party to compute the union, while preventing the leakage of any other extra information. This includes protecting the origin and duplication of each data item across edge nodes, thus maintaining privacy in the IoT environment.